Ranking Factors Affecting the Attraction of Foreign Medical Tourists in Hospitals Affiliated to Mashhad University of Medical Sciences Based on Marketing Mix Model - Reza AZIMI; Ghahraman MAHMOUDI; Habib-Allah ESMAEILI (Tehran University of Medical Sciences, 2018)
Background: This study was designed to rank factors affecting attraction of foreign medical tourists based on marketing mix model. Methods: In this descriptive study, data were collected through a questionnaire. Foreign patients, hospitalized from Jan 2015 to Sep 2016 in all hospitals of Mashhad were chosen as the study population (13 hospitals). Data analysis was conducted using Friedman test and Wilcoxon test in SPSS 21 at a significance level of 0. 05. Results: Factors of staff, service and process gained the highest score from the perspective of patients; while price, facilities and promotion scored the lowest among parameters affecting the attraction of medical tourists to hospitals of Mashhad. In this context, factors of staff (96%) and price (66%) had the highest and lowest effect on absorption of tourists, respectively. Conclusion: To promote medical tourism, important factors such as staff, service, and process should be further stressed and variables of price, facilities and promotion demand for a revision by the authorities in this industry.